Analisis Penggunaan Digital Payment QRIS pada Pelaku Usaha Mikro dan Kecil - Sastra, Abelya; Asyari (Jurnal Ilmiah Administrasi Bisnis dan Inovasi, 2024)
The aim of this research is to find out how the behavior of using QRIS digital payments by micro and small businesses (UMK) in the city of Bukittinggi is analyzed using the UTAUT method using four research constructs, namely performance expectancy, effort expectancy, social influence and facilitating conditions and adding one The moderating variable is knowledge about QRIS digital payments. Data collection was obtained by distributing questionnaires to 100 respondents to MSEs who had used digital payment QRIS which met several criteria and analyzed using SEM-PLS with the help of WarpPLS 3 software. The results in this study showed that of the four main contracts using the UTAUT method, only social influence had a significant influence. significant impact on the use of QRIS digital payments by MSEs. Meanwhile, performance expectancy, effort expectancy and facilitating conditions were found to have no significant effect on the use of QRIS digital payments by MSEs. Furthermore, different results were shown in the UTAUT method construct after being given the moderating variable of QRIS digital payment knowledge, namely that there were three contract variables: performance expectancy, social influence and facilitating conditions had a significant effect on the use of QRIS digital payments and the effort expectancy variable was moderated by QRIS digital payment knowledge. The use of digital payment QRIS shows insignificant results. Keywords: Digital Payment, QRIS; UTAUT ; Micro and Small Enterprises